ANALISIS INSTRUMEN DIAGNOSIS KESEHATAN PENGORGANISASIAN SUMBER DAYA DI LEMBAGA DIKLAT - Rani Ramadhani (Universitas Pendidikan Indonesia, 2021)
In general, this research aims to construct the instrument of health diagnostic of organizing resources specifically in training institute, which is used to overcome a problem or confusion experienced by the head of the institute in analyzing the organizing function. The method used in this research is a descriptive method with a quantitative approach. The techniques used in compiling the instruments made up of three stages. The first stage is conducting the constructed test by revising the question items assisted with the lecturer. The second stage is constructing tests given to the respondents through questionnaires distribution to PPPPTK IPA, PPPPTK BMTI, and PPPPTK TK and PLB with the help of Google Form. Finally, the third stage consists of various tests, such as the validity test, reliability test, and Weight Mean Score. The total population is 278 and the number of samples is 165. This research used a proportional stratified random sampling technique. Based on the calculation, the total respondent in this research is 167 with the r table and the reliability test obtained are 0.1277 and 0.933 respectively. As to the health resources organizing in PPPPTK IPA, PPPPTK BMTI and PPPPTK TK and PLB can be pictured in a